Seeing Ourselves Through Technology How We Use Selfies, Blogs and Wearable Devices to See and Shape Ourselves - Walker Rettberg, Jill (Springer Nature, 2014)
Cultural and Media Studies, New Media and Digital Media, Media and Cultural Theory, Popular Culture